2021
DOI: 10.1177/00438200211013017
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion Through Inclusion: Institutional Constraints on Women's Political Empowerment in India and Bangladesh

Abstract: This comparative case study uses qualitative data to explore and analyze the institutional obstacles that women in reserved seats face to their political empowerment in the Gram Panchayat in India and the Union Parishad in Bangladesh. The findings reveal that women in reserved seats in both countries confront some fundamental institutional barriers, such as a masculine model of politics, lack of political party support, as well as lack of power and resources. Indian women face serious problems—the inclusion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
(94 reference statements)
0
7
0
Order By: Relevance
“…All of their views go against women's engagement in politics. They also confidently expressed that, except for very few exceptions, women MPs cannot perform by themselves and very often engage their friends and relatives in the dispensation of their functions as elected representatives (Prodip 2021). Women are still rarely considered as full political actors and are rather seen as pawns to be used in the political maneuvers of men—a position that Collier (1974, 89) drew attention to long ago.…”
Section: Supply‐side Factorsmentioning
confidence: 99%
“…All of their views go against women's engagement in politics. They also confidently expressed that, except for very few exceptions, women MPs cannot perform by themselves and very often engage their friends and relatives in the dispensation of their functions as elected representatives (Prodip 2021). Women are still rarely considered as full political actors and are rather seen as pawns to be used in the political maneuvers of men—a position that Collier (1974, 89) drew attention to long ago.…”
Section: Supply‐side Factorsmentioning
confidence: 99%
“…The other two studies (Chowdhury 2001;Panday 2008) were based on secondary resources only. Recently, Prodip (2021aProdip ( , 2021b found that quota-elected women in India and Bangladesh have failed to exercise their voice in the decision-making process in a more egalitarian manner due to clear institutional and cultural challenges. Hence the present study contributes to filling the gap in our understanding of women's political participation in the two countries by identifying the socio-economic barriers that the women in reserved seats face with regards to their political empowerment.…”
Section: Socio-economic Barriers To Women's Political Participationmentioning
confidence: 99%
“…This is because some factors-especially underexplored dimensions of quota design-actually restrict quota-elected women in their ability to introduce, influence, or change policy (Clayton 2021). Prodip (2021aProdip ( , 2021b, for instance, found that variations in the institutional design of gender quotas and patriarchy often limit the ability of quota women to introduce durable women-friendly policies in political legislatures. This is particularly so in some parts of the developing world.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The focus remains on Asia in the next two articles. Khan and Ara (2023) examine the key reasons why so few women are running in Bangladesh's parliamentary elections, making a useful addition to prior articles in this journal focusing on gender and politics in Asia (see, e.g., Prodip 2021). Rubiolo and Aguirre (2023) address South Korea's foreign policy toward ASEAN from a middle-power perspective.…”
mentioning
confidence: 99%